Plant litter mixture partly mitigates the negative effects of extended drought on soil biota and litter decomposition in a Mediterranean oak forest. (4th January 2017) - Santonja, Mathieu; Fernandez, Catherine; Proffit, Magali; Gers, Charles; Gauquelin, Thierry; Reiter, Ilja M.; Cramer, Wolfgang; Baldy, Virginie
Summary: A major challenge of current ecological research is to determine the responses of plant and animal communities and ecosystem processes to future environmental conditions. Ecosystems respond to climate change in complex ways, and the outcome may significantly depend on biodiversity. We studied the relative effects of enhanced drought and of plant species mixture on soil biota and on litter decomposition in a Mediterranean oak forest. We experimentally reduced precipitation, accounting for seasonal precipitation variability, and created a single‐species litter ( Quercus pubescens ), a two‐species litter mixture ( Q. pubescens + Acer monspessulanum ) and a three‐species litter mixture ( Q. pubescens + A. monspessulanum + Cotinus coggygria ). In general, drier conditions affected decomposers negatively, directly by reducing fungal biomass and detritivorous mesofauna, and also indirectly by increasing the predation pressure on detritivorous mesofauna by predatory mesofauna. This is reflected under drier conditions in that Collembola abundance decreased more strongly than Acari abundance. One Collembola group (i.e. Neelipleona) even disappeared completely. Increased drought strongly decreased litter decomposition rates. Mixed litter with two and three plant species positively affected soil biota communities and led to a more efficient litter decomposition process, probably through a greater litter quality. Faster decomposition in mixed litter can thus compensate slower decomposition rates under drier condition. Synthesis . Our results highlight that, within our study system, drier climate strongly impacts on soil biodiversity and hence litter decomposition. Species‐rich litter may mitigate such a decline in decomposition rates. Diverse plant communities should hence be maintained to reduce shifts in ecosystem functioning under climate change. Abstract : We studied the relative effects of aggravated drought and of plant species mixture on soil biota and on litter decomposition in a Mediterranean oak forest. Drier climate strongly reduced soil biodiversity and litter decomposition rates. However, species‐rich litter partly mitigated such a decline. Diverse plant communities should hence be maintained to reduce shifts in ecosystem functioning under climate change.